The Impact of English and Indigeneous Languages on the Learning of French: The Case Study of the Nigerian French Language Village, Badagry - Musa, Esther Amiemenomoh; Gandu, Rautha Charity (NIU Journal of Humanities, 2023)
This research is to excavate the causes of students’ inability to communicate effectively in French language without mixing it up either with English language or their mother tongue amongst tertiary students. The Nigerian French Language Village (NFLV) has been chosen as a case study. The Language village is the center for language emersion of French language students. Different Nigerian universities, Polytechnics and Colleges of Education send their students there for minimum of six (6) months with the hope of getting better in their level of spoken and written French. This research seeks to establish that the spoken aspect of a language is very vital in the learning of a foreign language. The study lay emphases on effective oral communication amongst students in a bilingual environment and in the same vein recommends some pedagogical techniques in enhancing and promoting effective oral communication in French. Keywords: Language, French, English, Indigenous Language, Impact